PENGARUH THIN CAPITALIZATION, CAPITAL INTENSITY, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Rizal Rahmat Cahyadi; Achmad Tjahjono (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to determine the effect of thin capitalization, capital intensity, and profitability on tax avoidance with institutional ownership as moderation. The population in this research consists of mining sector companies that were listed on the IDX during the 2019-2023 period. The sample in this study used purposive sampling method and obtained 20 companies. The research utilizes secondary data, analyzed using descriptive statistical methods and MRA. The findings reveal that thin capitalization does not influence tax avoidance, whereas capital intensity and profitability exhibit a significant positive impact on tax avoidance. Furthermore, institutional ownership is unable to moderate the relationship between thin capitalization and tax avoidance. However, institutional ownership effectively weakens the influence of capital intensity and profitability on tax avoidance. The lesson we can take is that companies need to manage capital intensity and profitability transparently to reduce the risk of tax avoidance and audit. Institutional ownership acts as an effective supervision that can weaken the impact of these two variables, so it needs to be improved in corporate governance.